Application of slag refining technique to metallurgical grade silicon purification process: A review - Rowaid Al-khazraji; Yaqiong Li; Lifeng Zhang (Functional Materials, 2018)
The photovoltaic generates electricity through direct conversion of sunlight, has fast-growing recently due to high global energy demand. Photovoltaic main material is silicon which needs refining process to fulfill the requirements. In this paper, the principle of silicon-slag refining was introduced and several types of imposing slag were reviewed. Boron removal from silicon using Si-based alloy and novel slag with active component were mentioned, and effects of slag refining processing parameters were discussed. According to the investigations, slag refining technique can remove a large amount of boron from MG-Si, and the potential industrial applications of slag refining technique were proposed.